The effect of corporate governance and firm size on companys financial performance - Richy Sugiono Agus Budiyanto; Gunasti Hudiwinarsih (STIE Perbanas Surabaya, 2015)
The company's financial performance is very important, as one of the ways that can be done by the company's management, to meet the obligations of the parties concerned in achieving the vision and mission of the company. Good Corporate governance is one way to make the company more optimal in achieving the goals of the company. Based on the Corporate Governance Perception Index, some companies are included in the CGPI ratings with the category of very reliable and reliable. This will bring more investors to come so that the companies can develop into bigger investment with funds provided by the investors. As such, the research aims to test the effect of good corporate governance, as measured by CGPI score and firm size on the companys financial performance, con-sisting of profitability, leverage, and liquidity. This research is using purposive sampling method to select all the population, i.e. companies included in the CGPI ratings with the category of very reliable and reliable, and listed in Indonesia Stock Exchange period 2010-2013. There are 59 companies used as the samples in this study. The results of the analysis show that good corporate governance affects profitability and leverage, but it does not affect liquidity. While, firm size affects profitability, leverage, and liquidity